Analysis of triptan use during pregnancy in Japan: A case series. (13th January 2022) - Yamaguchi, Yuko; Yamada, Takahiro; Goto, Mikako; Kawasaki, Hidenori; Wada, Takahito; Ikeda‐Sakai, Yasuko; Saito, Yoshiyuki; Hayashi, Masahiro; Tanaka, Shiro; Takahashi, Ryosuke; Nakayama, Takeo; Murashima, Atsuko; et al.
Abstract: To evaluate the safety of triptan use during pregnancy in a Japanese population, we descriptively analyzed the data on pregnancy and fetal outcomes from 128 pregnant women using triptans for migraine treatment at two Japanese facilities that provided counseling on drug exposure in pregnancy between 2001 and 2017. The risks of miscarriage, low birth weight, and preterm birth were similar to those reported in the demographic statistics in Japan. The incidence proportion of malformation was also within the baseline risk range. Accumulated data suggest that exposure to triptans during pregnancy does not clearly increase the risk of negative pregnancy and fetal outcomes. This finding can help reduce anxiety in pregnant women with migraines who are taking triptans.